Collaborative narrative generation in persistent virtual environments - Madden, Neil (2009)
This thesis describes a multi-agent approach to generating narrative based on the activities of participants in large-scale persistent virtual environments, such as massivelymultiplayer online role-playing games (MMORPGs). These environments provide diverse interactive experiences for large numbers of simultaneous participants. Involving such participants in an overarching narrative experience has presented challenges due to the difficulty of incorporating the individual actions of so many participants into a single coherent storyline. Various approaches have been adopted in an attempt to solve this problem, such as guiding players to follow pre-designed storylines, or giving them goals to achieve that advance the storyline, or by having developers (‘dungeon masters’) adapt the narrative to the real-time actions of players. However these solutions can be inflexible, and/or fail to take player interaction into account, or do so only at the collective level, for groups of players.